Do age‐associated DNA methylation changes increase the risk of malignant transformation?. (9th October 2014) - Wagner, Wolfgang; Weidner, Carola I.; Lin, Qiong
<x xml:space="preserve">Abstract</x> Aging of the organism is associated with highly reproducible DNA methylation (DNAm) changes, which facilitate estimation of donor age. Cancer is also associated with DNAm changes, which may contribute to disease development. Here, we speculate that age‐associated DNAm changes may increase the risk of tumor initiation. Notably, when using epigenetic signatures for age‐estimations tumor cells are often predicted to be much older than the chronological age of the patient. We demonstrate that aberrant hypermethylation within the gene DNA methyltransferase 3A (DNMT3A) – which may contribute to initiation of acute myeloid leukemia (AML) – is particularly observed in AML samples that reveal significantly more age‐associated DNAm changes. The functional relevance of age‐associated DNAm changes remains to be elucidated, but they occur genome wide, in a highly reproducible manner, and most likely influence chromatin organization – and hence may favor acquisition of aberrant DNAm patterns contributing to cancer in the elderly.